Community Development as Disaster Risk Reduction Efforts through the Disaster Resilient Village (Destana) Program in Nganjuk Regency - Novianti Luluk Mahbubah; Mochamad Faizal Rizki; Haura Atthahara (Universitas Muhammadiyah Malang, 2021)
The high disaster risk index in Nganjuk District shows the magnitude of potential casualties and the impact of the emergence of disasters that have occurred. That is because Nganjuk Regency is one area that has a high potential for catastrophic threats with low land and mountain topography, causing several disasters such as floods, landslides, land and forest fires, drought and strong winds / whirlwinds plus still low public knowledge in disaster management. Therefore the Regional Government through the Badan Penanggulangan Bencana Daerah (BPBD) Nganjuk District is implementing the Desa Tangguh Bencana (Destana) program in disaster-prone villages in Nganjuk Regency. Where the Destana program is a community development activity to reduce the risk of existing disasters so that the community is expected to be resilient in the face of disasters. In research using qualitative research methods with a descriptive approach. Data collection techniques used were field observations, in-depth interviews, and documentation. The results of this study indicate that the Destana program established by the BPBD Nganjuk District by developing disaster-prone communities has been able to reduce the risk of existing disasters by forming resilient and independent communities in the face of disasters.